Combined analysis of proteomics and metabolism reveals critical roles of oxidoreductase activity in mushrooms stimulated by wolfberry and sea buckthorn substrates - Yuan Zhao; Hongying Li; Youhua Yao; Youhua Yao; Qing Wei; Tilong Hu; Xia Li; Boxu Zhu; Hailing Ma (Frontiers in Nutrition)
BackgroundCultivating edible fungi, particularly Lentinula edodes, efficiently transforms agroforestry byproducts into valuable products. However, the mechanism of the promotive effects of those substrates was largely unknown. This study used wolfberry (WB) and sea buckthorn (SBK) substrates to investigate mushroom fruiting bodies’ physiological, proteomics, and metabolism profiling.ResultsResults show that compared to apple wood (AW), the crude protein and fatty acids were substantially enhanced by both WB and SBK treatment. We identified 1409 and 1190 upregulated and downregulated differentially abundant proteins (DAPs) for the SBK versus AW group and observed 929 overlapped DAPs with upregulation patterns. Of these DAPs, carbohydrates and oxidoreductase activity pathways were significantly enriched. Moreover, the enhanced expression of nine genes by WB and SBK was confirmed by qPCR. Metabolism suggests that 66 differentially abundant metabolites overlapped in the list of two comparison groups (WB versus AW and SBK versus AW).ConclusionCollectively, we summarized that both WB and SBK stimulate glucose degradation, enhance the expression of gene-related oxidoreductase activity, and promote protein biosynthesis by coordinating with amino acid metabolism. This study highlights the importance of oxidoreductase activity in promoting nutritional value in mushroom fruiting bodies induced by WB and SBK substrates.